Multi-stage, complicated lead-dependent infective endocarditis treatment: good and bad decisions - Kutarski, Andrzej; Pietura, Radosław; Czajkowski, Marek; Tomaszewski, Andrzej (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Indications to surgical treatment of patients with lead-dependent infective endocarditis are clearly defined in guidelines, but technical and logistic issues are not given precisely. The present state of knowledge about pathophysiology of patients’ reaction to pacemakers and leads shows that preoperative percutaneous lead evacuation or at least complete liberation inside the venous system before a surgical intracardiac procedure is an optimal solution. Complete lead removal through the right atrium is often impossible and partial removal is a potential source of infective endocarditis. The case is an illustration of this sad truth.